Exploring the Documentation and Preservation of African Indigenous Knowledge in a Digital Lexical Database - Bosch, Sonja E.; Griesel, Marissa (Lexikos, 2020)
Transcending the boundaries of printed lexicographic resources is becoming easier in the digital age, with e-resources facilitating restrictions on the size and type of information that can be included. In this article we explore innovative ways of documenting and preserving African indigenous knowledge, often underrepresented in traditional dictionaries, in an existing digital lexical database. Our approach is based on the extension of the African Wordnet, a lexical database under construction for nine African languages, in this case applied to isiZulu. This article addresses the challenge of consolidating dispersed indigenous knowledge collected from a variety of sources such as conventional dictionaries, interdisciplinary publications and a flat-structured online database, in a digitised hierarchical wordnet structure. A representative sample of traditional domestic utensils in Zulu culture is used to demonstrate the conversion into a set of typical semantic relations in a wordnet structure. By focusing on filling lexical gaps between isiZulu and English as found in the Princeton WordNet, with culturally relevant synsets, the African Wordnet also becomes a useful resource for natural language processing. Finally, it is shown how the hierarchical classification of selected domestic utensils is visually presented in wordnet graphs in the WordnetLoom interface.